Acute myeloid leukemia with inv(3)(q21q26.2) or t(3;3)(q21;q26.2): Clinical and biological features and comparison with other acute myeloid leukemias with cytogenetic aberrations involving long arm of chromosome 3. Issue 8 (September 2015) - Raya, Jose Maria; Martín-Santos, Taida; Luño, Elisa; Sanzo, Carmen; Perez-Sirvent, Maria Luz; Such, Esperanza; Navarro, José Tomás; Millá, Fuensanta; Alonso, Esther; Domingo, Alicia; Rozman, María; Díaz-Beva, Marina; et al.
Abstract : Objectives : To compare, from a biological and clinical perspective, a significant group of patients with AML with inv(3)(q21q26.2) or t(3;3)(q21;q26.2) with another group of AML carrying different abnormalities of 3q at q21 or q26, the latter named as the AML abn(3q) group.Methods : We developed a national survey with the participation of 13 Spanish hospitals, and retrospectively reviewed (from 1990 to 2010) these subtypes of AML. Fifty-five patients were collected: 35 with AML inv(3)/t(3;3) and 20 with AML abn(3q). A data collecting page that included main features at diagnosis, therapeutic approach and response, and survival variables, was distributed and completed.Results : We did not find significant differences in sex, age, history of myelodysplastic syndrome or chemo-/radiotherapy, clinical presentation, WBC and platelet counts, hemoglobin level, blasts immunophenotype, serum lactatedehydrogenase, peripheral blood and bone marrow cellular dysplasia, and bone marrow biopsy findings. Although the association with monosomy 7 was significantly more frequent in AML inv(3)/t(3;3), this did not seem to influence outcome. The lack of response to the different modalities of treatment and the aggressive course of the disease were the standard in both cohorts of patients.Discussion : Although not yet recognized by the World Health Organization classification, our results are in agreement with the findings of other authors, who include both subsets of AML together in the same group of adverse prognosis.Conclusion : In an attempt to simplify and bound entities with similar genetic background and clinical behavior, it would be desirable to bring together both subgroups of AML in a single section.